Effects of energy supplements on the differentiation of skeletal muscle satellite cells. Issue 1 (13th December 2020) - Su, Rina; Wang, Bohui; Zhang, Min; Luo, Yulong; Wang, Debao; Zhao, Lihua; Su, Lin; Duan, Yan; Faucitano, Luigi; Jin, Ye
Abstract: To investigate the effects of the activator of AMPK and high glucose on the differentiation of mouse SMSCs, primary SMSCs were isolated from mouse extensor digitorum longus muscle and grown to near confluence (80%). Postconfluent cells were cultured in a growth medium with different inductors: AICAR, glucose, and AICAR mixed with glucose. The specific protein expressions of SMSCs, myoblasts, adipocytes, and brown adipocytes were analyzed on days 0, 3, 5, 7, and 10. The results showed treatment with AICAR in SMSCs markedly activated AMPK phosphorylation ( p < .05) and increased protein expression of Pax7 and MyoD ( p < .05), high concentrations of intracellular glucose upregulated UCP‐1 protein expression and enhanced lipid accumulation ( p < .05), the cowork of AICAR and glucose affected a decrease on MyoD, PPARg, and UCP‐1 expression ( p < .05) and an increase on Pax7. The present study indicated that the certain energy supplements influence the direction of SMSC differentiation which may contribution on the structure of muscle and meat quality, sequentially. Abstract : To investigate the effects of the activator of AMPK and high glucose on the differentiation of mouse SMSCs, primary SMSCs were isolated from mouse extensor digitorum longus muscle and grown to near confluence (80%). Postconfluent cells were cultured in a growth medium with different inductors: AICAR, glucose, and AICAR mixed with glucose. The present study indicated that the certain energy supplements influence the direction of SMSC differentiation which may contribution on the structure of muscle and meat quality, sequentially.